Isolated methylmalonic acidemia with unusual presentation mimicking diabetic ketoacidosis - Prapai Dejkhamron (2018)
© 2016 by De Gruyter. Background: Hyperglycemic ketoacidosis is an acute, life threatening condition requiring early etiologic recognition and management to prevent serious morbidity/mortality. The most common cause is diabetic ketoacidosis (DKA). Organic acidemias (OAs) are inheritable disorders caused by defects in protein metabolism resulting in acid accumulation. Patients with metabolic decompensation usually present with acidosis, with/without hypoglycemia. Hyperglycemia is a very rare manifestation. At least 16 cases of OAs presenting with hyperglycemia have been reported. Six of the 16 were diagnosed with isolated methylmalonic academia (MMA) and three of the six passed away from late diagnosis. Case description: We describe a 2-year-old Thai girl who presented with hyperglycemia, acidosis and ketosis. She has underlying delayed development, seizures, optic atrophy and poor growth. An initial diagnosis of DKA was made and standard treatment was started. After 4 h of treatment, the patient partially responded to treatment; blood sugar decreased but acidosis and ketonemia persisted. HbA1c was normal. Investigations to rule out OAs were performed. Markedly elevated urinary methylmalonic acid consistent with MMA was observed. Molecular and enzyme analyses confirmed the diagnosis with isolated MMA. Specific treatment for MMA including protein restriction, high caloric fluid, carnitine and vitamin B12 was promptly started. Clinical improvement was seen 4 days after initiating specific treatment. Conclusions: Inherited metabolic disorders should be included in differential diagnosis in hyperglycemia ketoacidosis patients who respond poorly to standard DKA treatment. Unusual findings, e.g. hyperammonemia, lactic acidosis, pancytopenia, abnormal basal ganglia in MRI or underlying delayed development may indicate underlying OAs. Determining the etiology of hyperglycemic ketoacidosis is important and can lead to good outcomes.